2022
DOI: 10.3389/fcimb.2022.909507
|View full text |Cite
|
Sign up to set email alerts
|

The Orphan Response Regulator Rv3143 Modulates the Activity of the NADH Dehydrogenase Complex (Nuo) in Mycobacterium tuberculosis via Protein–Protein Interactions

Abstract: Two-component signal transduction systems enable mycobacterial cells to quickly adapt and adequately respond to adverse environmental conditions encountered at various stages of host infection. We attempted to determine the role of the Rv3143 “orphan” response regulator in the physiology of Mycobacterium tuberculosis and its orthologue Msmeg_2064 in Mycobacterium smegmatis. We identified the Rv3143 protein as an interaction partner for NuoD, a member of the type I NADH dehydrogenase complex involved in oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…MSMEG_2064 is found in the same operon as other Complex I genes 5′ of nuoA and was proposed to be a constituent of mycobacterial Complex I (12). Furthermore, recent crosslinking experiments suggested that MSMEG_2064 associates with NuoD and deletion of the MSMEG_2064 gene affects expression of some electron transport chain components (51). The structure of MSMEG_2064 predicted by AlphaFold (52) fits into the unidentified density with high fidelity (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MSMEG_2064 is found in the same operon as other Complex I genes 5′ of nuoA and was proposed to be a constituent of mycobacterial Complex I (12). Furthermore, recent crosslinking experiments suggested that MSMEG_2064 associates with NuoD and deletion of the MSMEG_2064 gene affects expression of some electron transport chain components (51). The structure of MSMEG_2064 predicted by AlphaFold (52) fits into the unidentified density with high fidelity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MSMEG_2064 is a two-component response regulator protein that is considered to be an “orphan” because its cognate kinase has not been identified (51, 53). Sequence comparison and structural alignment with the PDBeFold server (54, 55) showed similar folds but low sequence identity (<30%) between MSMEG_2064 and other two-component response proteins with known structures.…”
Section: Resultsmentioning
confidence: 99%
“…mtrA is essential in Mtb due its role in replication, whereas in Mab mtrA was reported to be non-essential, pointing to potential differences in the role of this TCS between the two species ( Fol et al., 2006 ; Akusobi et al., 2022 ). The Mtb ortholog (Rv3143) of orphan RR Mab _ 2133 is implicated in nitrate metabolism in the absence of oxygen, binds to nuo subunits required for electron transport and is within nuo operon ( Plocinska et al., 2022 ). Mab’s nuo operon displays synteny with the Mtb nuo operon including the orphan RR Mab _ 2133 .…”
Section: Resultsmentioning
confidence: 99%